Evaluation of nested network mobility approaches - Ali Mohammed, Mohammed Babiker; Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina (2014)
Recently, wireless devices have been used significantly due to the continuous and enormous Services that they provide. One of the major challenges that faces is how to achieve high network performance. The Internet Engineering Task Force (IETF) has developed Mobile IP, which allows Mobile node to be connected while it is moving as well as functioning in foreign mobile network zone using its original IP address. IETF also in order to manage mobility of an entire network as single unit, they developed NEMO Basic Support Protocol (NEMO BS), which allows Mobile Router to move and change their point of attachment. When a Mobile Router connected to other mobile router on foreign mobile network, it makes a hierarchical structure known as Nested Mobile Network. When the level of nesting becomes high, problems of tunneling overhead, handoff latency, packet losses and complexity are increased which will cause inefficiency and bad Performance. The purpose of this paper is an attempt to evaluate the current approaches and the proposed solutions that dealt with these issues.